ANALISIS YURIDIS AGUNAN BERUPA ASET KRIPTO DALAM PENERAPAN PRINSIP 5C PEMBERIAN KREDIT PERBANKAN - Kirana, Anggun (JURNAL AKTA YUDISIA, 2024)
This research will examine from a juridical perspective whether crypto assetscan be used as collateral in the application of the 5C principles of banking creditissuance. This research is a normative legal study that employs a statutoryapproach. The primary legal materials used include the Civil Code, Law Number10 of 1998 concerning Amendments to Law Number 7 of 1992 on Banking, LawNumber 32 of 1997 on Commodity Futures Trading, Law Number 42 of 1999 onFiduciary Guarantees, and secondary legal materials such as books, journals, andthe findings of other research related to the issue. The results of this studyindicate that crypto assets can be used as collateral in banking credit issuance,either through pawn or fiduciary institutions, each of which has its owncharacteristics. Therefore, the appropriate collateral institution will depend onthe preferences of the debtor and the creditor. It is important to identify legalrisks and other associated risks, such as price fluctuations, so that crypto assetscan be used as additional collateral rather than primary collateral.Keywords: Aset Kripto, Prinsip 5C, Kredit Perbankan